2020
DOI: 10.1080/16078454.2020.1833506
|View full text |Cite
|
Sign up to set email alerts
|

Diaphragm ultrasonography in adults with sickle cell anemia: evaluation of morphological and functional aspects

Abstract: Objectives: To assess morphological and functional aspects of the diaphragm by ultrasonography (US) in adults with sickle cell anemia (SCA) and evaluate if the diaphragmatic musculature can play a role in changes found in pulmonary function tests (PFTs) of these patients. Methods: This is a cross-sectional observational and single-center study involving 40 adults with SCA who underwent diaphragm US and PFTs with a maximum of 1 month between the two tests. Diaphragm US was performed in B and M modes, and echoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…In patients suffering from COPD, not only will the diaphragmatic muscle reduce its excursion but will have a preference for the inspiratory position; in patients with chronic heart failure the diaphragm mass becomes thinner with smaller respiratory excursions [8, 51]. In patients with anemia, the right portion of the diaphragm has a greater excursion than the left area, the opposite compared to healthy subjects [52]. In healthy elderly subjects, the diaphragm muscle reduces its strength and the ability to induce effective intra-abdominal pressure by about 20–41%, decreasing the excursion efficiently.…”
Section: Movement Of the Diaphragm During The Eupneic Ventilationmentioning
confidence: 99%
“…In patients suffering from COPD, not only will the diaphragmatic muscle reduce its excursion but will have a preference for the inspiratory position; in patients with chronic heart failure the diaphragm mass becomes thinner with smaller respiratory excursions [8, 51]. In patients with anemia, the right portion of the diaphragm has a greater excursion than the left area, the opposite compared to healthy subjects [52]. In healthy elderly subjects, the diaphragm muscle reduces its strength and the ability to induce effective intra-abdominal pressure by about 20–41%, decreasing the excursion efficiently.…”
Section: Movement Of the Diaphragm During The Eupneic Ventilationmentioning
confidence: 99%
“…Interestingly, Zeitoune et al 14 reported that in adults with SCD, respiratory muscle strength was impaired even though diaphragm thickness via ultrasonography was similar compared to healthy controls. However, diaphragm excursion was higher in the SCD group 14 . These findings may suggest that there are potential differences in ventilatory strategies owing to structural and functional changes in the diaphragm.…”
Section: Introductionmentioning
confidence: 99%
“…However, diaphragm excursion was higher in the SCD group. 14 These findings may suggest that there are potential differences in ventilatory strategies owing to structural and functional changes in the diaphragm. However, diaphragm function has not been well-studied in children with SCD and whether it affects ventilatory parameters such as respiratory frequency (f R ) and tidal volume (V T ) during exercise is not known.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Diaphragm dysfunction is associated with dyspnea, decreased exercise endurance and quality of life 13 . Ultrasound is considered as an optimal tool to evaluate the diaphragmatic thickness and function in multiple diseases because of its high sensitivity and specificity, combined with zero radiation and low cost 14 17 . Ultrasound-assessed diaphragm dysfunction is reliable in early identifying diaphragm atrophy and stratifying patients’ risk of worse prognosis 18 22 .…”
Section: Introductionmentioning
confidence: 99%